American Hospital Association guide to the health care field.
Annual. Basic reference source on hospitals in the United States. Also includes information on the American Hospital Association, health organizations and agencies, statistics, educational programs, and sources of products and services used in hospitals. Geographical arrangement of hospitals. Entry gives descriptive information, e.g., services offered, number of beds, and number of births. Index.